Growth Mindset Profile of Elementary School Teachers in Denpasar City Reviewed from Length of Service - Santhi, Putu Prema Jaya; Riastini, Putu Nanci; Werang, Basilius Redan (Mimbar Ilmu, 2024)
The mover school program, especially the school human resource strengthening program that has been followed by teachers, is expected to have an impact on the growth mindset of teachers. However, in reality, teachers have not yet maximally possessed growth mindset, so it needs to be improved by carrying out an activity that specifically discusses the topic of growth mindset. In addition, the length of service of teachers also has an impact on teacher performance (in this case the growth mindset of teachers). The purpose of this study was to describe the growth mindset profile of teachers of school drivers in Denpasar City in terms of length of service. This type of research is quantitative descriptive research. The research sample was 46 elementary school teachers representing five groups of length of service (<5 years, 5-10 years, 11-15 years, 16-20 years, >20 years). Research data were collected using non-test techniques in the form of questionnaires. The research instrument adopted the mindset quiz instrument by Carol Dweck, which consisted of 20 statements with 4 answer choices. The collected data were analyzed using descriptive statistics. The results of this study found that the growth mindset profile of teachers at mover schools in Denpasar City is generally dominated by a growth mindset with some fixed ideas, and the growth mindset profile of teachers at mover schools in Denpasar City reviewed from the length of service is dominated by a growth mindset with some fixed ideas. The results of this study will have implications for the selection/implementation of teacher quality empowerment programs, especially programs to improve teacher growth mindset.